ENT600: Smart Ergonomic Table (S.E.T) / Fatin Shafikah Ribuan … [et al.] - Ribuan, Fatin Shafikah; Abu Bakar, Nor Aziyati; Mohd Nor Azmi, Nur Afiqah; Mohd Salleh, Nurul Syuhada; Saad, Siti Hajar (2018)
In this developing era, all the things that we do are involving technology. Nowadays, there are increasing statistics about people which prefer reading on the screen rather than reading on the papers since our dependence on computers has grown. This can lead to a health problem called Computer Vision Syndrome (CVS). CVS describes eye-related and other problems caused by prolonged computer use. In medical circles, it is much said that the eyes lead the body because vision is the most powerful determinant of posture. The issues arises is due to prolonged computer use. For example, reading stand is still in traditional and classic design. Although we are aware that ergonomic stands have been invented, but there is still lack some of the important and technology features. The idea is to turn a classic reading stand into a Smart Ergonomic Table (S.E.T) where the technology is implementing in this product. New product development is a multi-stages process of developing a new product to the marketplace. The new product can be classified into two categories which are completely new products and improvements on the existing products. S.E.T is an improvement on the existing products because S.E.T allows the company to enter the market by undergoing some significant improvements in terms of technology and it features. The company visualized as many ideas as possible since research and development process of ideation is gone through idea generation. In addition, the company is then narrowed down the ideas' and chooses S.E.T as a new product. This stage is called as idea screening stage. Lastly, market survey is conducted to analyze consumers' needs and preferences. Hence, 96% of the respondents found that S.E.T is an interesting product. The company set an online survey about the product (S.E.T) and 105 respondents were took part in the online survey. Based on the survey conducted, it can be concluded that S.E.T is accepted and highly demanded in the current market with the features. S.E.T made up from the best material and come along with the other interesting features that will ensure the potential customers will buy the product. On top of that, marketing strategy is necessary in order for planning the upcoming sales and product marketing activities and to ensure it will reach the targeted sales. We have implemented a few strategies that will be used for the test marketing. Furthermore, we have our own potential customers and location to market the S.E.T. Therefore, from the new product development survey, we strongly believe that S.E.T has the feasibility and viability in the market.